Phytophthora infestans Dihydroorotate Dehydrogenase Is a Potential Target for Chemical Control – A Comparison With the Enzyme From Solanum tuberosum - Garavito, Manuel F.; Narvaez-Ortiz, Heidy Y.; Pulido, Dania Camila; Löffler, Monika; Judelson, Howard S.; Restrepo, Silvia; Zimmermann, Barbara H. (Frontiers in Microbiology, 2019)
The oomycete Phytophthora infestans is the causal agent of tomato and potato late blight, a disease that causes tremendous economic losses in the production of solanaceous crops. The similarities between oomycetes and the apicomplexa led us to hypothesize that dihydroorotate dehydrogenase (DHODH), the enzyme catalyzing the fourth step in pyrimidine biosynthetic pathway, and a validated drug target in treatment of malaria, could be a potential target for controlling P. infestans growth. In eukaryotes, class 2 DHODHs are mitochondrially associated ubiquinone-linked enzymes that catalyze the fourth, and only redox step of de novo pyrimidine biosynthesis. We characterized the enzymes from both the pathogen and a host, Solanum tuberosum. Plant DHODHs are known to be class 2 enzymes. Sequence analysis suggested that the pathogen enzyme (PiDHODHs) also belongs to this class. We confirmed the mitochondrial localization of GFP-PiDHODH showing colocalization with mCherry-labeled ATPase in a transgenic pathogen. N-terminally truncated versions of the two DHODHs were overproduced in E. coli, purified, and kinetically characterized. StDHODH exhibited a apparent specific activity of 41 ± 1 µmol min-1mg-1, a kcatapp of 30 ± 1 s-1, and a Kmapp of 20 ± 1 μM for L-dihydroorotate, and a Kmapp= 30 ± 3 μM for decylubiquinone (Qd). PiDHODH exhibited an apparent specific activity of 104 ± 1 µmol min-1mg-1, a kcatapp of 75 ± 1 s-1, and a Kmapp of 57 ± 3 μM for L-dihydroorotate, and a Kmapp of 15 ± 1 μM for Qd. The two enzymes exhibited different activities with different quinones and napthoquinone derivatives, and different sensitivities to compounds known to cause inhibition of DHODHs from other organisms. The IC50 for A77 1726, a nanomolar inhibitor of human DHODH, was 2.9 ± 0.6 mM for StDHODH, and 79 ± 1 µM for PiDHODH. In vivo, 0.5 mM A77 1726 decreased mycelial growth by approximately 50%, after 92 hours. Collectively, our findings suggest that the PiDHODH could be a target for selective inhibitors and we provide a biochemical background for the development of compounds that could be helpful for the control of the pathogen, opening the way to protein crystallization.